Young children’s ideas of energy compared with the scientific energy concept: Results of a video study with interviews about children’s own drawings - Detken, Franziska (Frontiers in Education, 2023)
For accessing young children’s intuitive ideas about energy, twenty-five first and second graders of Swiss elementary schools (age 6-8 years, M = 7 years 6 months) were asked to draw or write what they associated with energy and subsequently interviewed about their drawing or written note. The responses were videotaped. The children’s responses, including gestures and other nonverbal responses, were analyzed using qualitative content analysis (QCA). A concept-driven approach was used to uncover links between the children’s ideas and the core aspects of the scientific energy concept: forms/manifestations, transformation, transfer, dissipation/degradation, and conservation, and a corresponding coding frame was developed. Though the participating children had not encountered energy or topics like electricity or human nutrition in formal schooling, almost all (N = 24) knew the term energy and used it in the interview. The findings indicate that already young children have nuanced ideas on how energy manifests and behaves that can be expressed by means of drawings/notes and verbally. These ideas refer to energy as an inherent feature of certain objects, as a causal agent, or as a kind of substance and are expressed in association with humans, electric sources and consumers, and vehicles, and their activities or features. The developed category systems summarize how young children express themselves about energy and enable comparison of these ideas with all core aspects of energy. The findings of this study indicate how the very first “steppingstones” for energy learning in early science classrooms might look like, and where “blind spots” or aspects that need further attention should be expected. The detailed analysis of the children’s statements with the developed coding frames is a first step towards reconstruction of the children’s mental models of energy and may serve as a basis for the development of educational and diagnostic tools.